The Chlamydia trachomatis Extrusion Exit Mechanism Is Regulated by Host Abscission Proteins - Zuck, Meghan (Microorganisms, 2019)
The cellular exit strategies of intracellular pathogens have a direct impact on microbial dissemination, transmission, and engagement of immune responses of the host. Chlamydia exit their host via a budding mechanism called extrusion, which offers protective benefits to Chlamydia as they navigate their extracellular environment. Many intracellular pathogens co-opt cellular abscission machinery to facilitate cell exit, which is utilized to perform scission of two newly formed daughter cells following mitosis. Similar to viral budding exit strategies, we hypothesize that an abscission-like mechanism is required to physically sever the chlamydial extrusion from the host cell, co-opting the membrane fission activities of the endosomal sorting complex required for transport (ESCRT) family of proteins that are necessary for cellular scission events, including abscission. To test this, C. trachomatis L2-infected HeLa cells were depleted of key abscission machinery proteins charged multivesicle body protein 4b (CHMP4B), ALIX, centrosome protein 55 (CEP55), or vacuolar protein sorting-associated protein 4A (VPS4A), using RNA interference (RNAi). Over 50% reduction in extrusion formation was achieved by depletion of CHMP4B, VPS4A, and ALIX, but no effect on extrusion was observed with CEP55 depletion. These results demonstrate a role for abscission machinery in C. trachomatis extrusion from the host cell, with ALIX, VPS4A and CHMP4B playing key functional roles in optimal extrusion release.